Distributions of extractable organic compounds in airborne paraticulate matter over the straits of Malacca, South China Sea and Sulu-sulawesi Seas / Aliaa Diyana Azizuddin - Aliaa Diyana, Azizuddin (2011)
The solvent-extractable hydrocarbons of 26 atmospheric samples, collected during a 2 months cruise starting from the Straits of Malacca, South China Sea and ends at Sulu- Sulawesi Seas were analyzed to determine the sources and distributions of homologous compounds series. The atmospheric aerosols were collected using a standard high volume air sampler at the rate of 1.13 m3/min for 24 hours. The filters with suspended particles were then extracted by ultrasonic agitation with dichloromethane and analyzed using gas chromatography-mass spectrometry. The particulate matter contains mainly fatty acids, n-alkanes and low levels of n-alcohols, n-aldehydes and aliphatic ketones derived from both natural and biomass burning emissions. Long chain aliphatic compounds were predominant in all the air particulate extracts, which could be attributed to terrestrial plant waxes. Aliphatic lipids from phytoplankton, algae and bacteria were also present in significant quantities.